2021
DOI: 10.1111/beer.12387
|View full text |Cite
|
Sign up to set email alerts
|

A puzzle about business ethics

Abstract: The following is a thought experiment. We believe that it can illustrate some of the strengths and weaknesses of the current body of research called "business ethics". In Section II we give our own response to the thought experiment and the possibilities therein.Consider the following:1. Suppose that a person, L, buys some raw material from a supplier and produces a product, P, that is, L and only L mixes her labor with the raw material to produce P. Suppose further that L will sell this product only to people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Although some scholars have suggested that business theory and perhaps even business ethics are riddled with toxic concepts (Giacalone, 2004) and that studies of business ethics lack sufficient practicality (Freeman & Sollars, 2022), I am not convinced that the discipline is in such dire straits. That is not to say, however, that there are no grounds for concern regarding the long-term health of the study of business ethics.…”
Section: Virtue Ethics Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Although some scholars have suggested that business theory and perhaps even business ethics are riddled with toxic concepts (Giacalone, 2004) and that studies of business ethics lack sufficient practicality (Freeman & Sollars, 2022), I am not convinced that the discipline is in such dire straits. That is not to say, however, that there are no grounds for concern regarding the long-term health of the study of business ethics.…”
Section: Virtue Ethics Perspectivementioning
confidence: 99%
“…I now want to shift gears and to note a third problem that arises less from business ethics’ methodology (although it is in some ways related to the prevalence of social science approaches) and more from the lack of direct practical business experience on the part of business ethicists and management theorists. Business ethicists have been criticized for engaging in research that is largely irrelevant to practitioners (Freeman & Sollars, 2022; Giacalone, 2004). From an Aristotelian virtue ethics perspective, this criticism is especially damning, given that ethics must be practical or it ceases to be ethics (Aristotle, 1934).…”
Section: Part 3: Engaging In More Research With Immediate Practical I...mentioning
confidence: 99%
“…Business ethics educators, to sum up thus far, confront two intertwined problems: a general doubt that morals matter for business practice and a more specific uncertainty which ethical direction to take when encountering moral challenges in corporate decision-making (Freeman & Sollars, 2021). Either problem can only be solved in tandem with the other, as I will show below.…”
Section: Business Ethics In the Classroommentioning
confidence: 99%
“…Recently, Ed Freeman (with Gordon Sollars) 1 published a paper (2022) in which the reader was presented with a puzzle: has the academic discipline of business ethics that, on the surface, was such an immense success story, been asking the right questions? More ominously, has business ethics asked itself the most important question, namely, have we become a group of feckless activists caught in an elitist bubble?…”
Section: Introductionmentioning
confidence: 99%
“…My ideas go against the grain but they are not offered as a counter‐Truth, but as a conversation starter. That is because they are based on a conversation between Ed Freeman and myself about his paper with Gordon Sollars, and his review of his 1984 book on stakeholder management (2022). I would ask the reader to consider this: if I can make a somewhat plausible argument that Friedman and Freeman stand on a similar plank, would it not be better to explore the new questions this generates, rather than to discard or radically re‐interpret the scholarship of Ed Freeman as was done with the scholarship of Milton Friedman, just to be able to stick with old answers?…”
Section: Introductionmentioning
confidence: 99%